A Novel Single-Tube Next Generation Sequencing Assay for B-Cell Receptor Clonality Testing - Landon Pastushok; Shrutii Sarda; Karen Mochoruk; Wayne Hill; Loni T. Pickle; Michelle Toro; Carolina Gonzalez; Stephanie Ostresh; Timothy J. Looney; Chenchen Yang; Julie Stakiw; Mark J. Bosch; et al. (Journal of Molecular Pathology, 2024)
B-cell neoplasms possess clonal B-cell receptor rearrangements (BCR clonotype lineages) that can be identified by sequencing the B-cell repertoire for use in diagnostics, risk stratification, and high-sensitivity monitoring. BCR somatic hypermutation (SHM) can result in clonality detection failure from point mutations in PCR primer binding regions, often necessitating splitting samples into multiple reactions which increases test costs, turnaround times, and sample requirements. We evaluated the Oncomine BCR Pan-Clonality Assay, a novel single-tube PCR reaction that simultaneously amplifies all BCR loci for next-generation DNA sequencing, using neoplastic B-cell lines and clinical research samples from multiple myeloma (MM) patients, a plasma cell neoplasm associated with high SHM levels. The assay showed a linear detection range down to 1 ng of clonal DNA input, sensitivity to 10−6 in a polyclonal background, and high reproducibility. Clonotype lineages were identified in 42/45 (93%) MM samples. Ion Reporter software packaged with the assay permitted straightforward identification of MM subgroups. As expected, SHM was identified in 94% of MM cases, but several unexpected subgroups were identified including biased IGHV3-11 or IGHV4-34 usage in 20% of MM samples, and two cases with very low levels of SHM. Evidence of intraclonal diversity/ongoing SHM was identified in 18% of samples, suggesting a possible germinal center origin for some MM cases. The single-tube Oncomine BCR Pan-Clonality assay efficiently detects BCR clonotype lineages at rates comparable to existing multiple reaction assays and permits their characterization for cell of origin studies and lymphoma classification.